Circular RNAs are Potential Prognostic Markers of Head and Neck Squamous Cell Carcinoma: Findings of a Meta-Analysis Study - Nath, Moumita; Roy, Dibakar; Choudhury, Yashmin (Frontiers in Oncology, 2022)
Abstract Background: Several studies have reported the role of circRNAs in the pathogenesis, diagnosis and prognosis of different cancers. This meta-analysis study aimed to evaluate the potential of using circRNAs as prognostic biomarkers of head and neck squamous cell carcinoma (HNSCC). Methods: 816 relevant articles were retrieved from PubMed and Science Direct databases, out of which 17 met the inclusion criteria. These 17 studies were assessed for quality by the Newcastle-Ottawa Scale (NOS) system, and 9 high quality studies (NOS>7) were included in the meta-analysis. Cochran Q test and the I square (I2) metric were calculated to detect potential heterogeneity among studies. Sensitivity analysis was performed to validate the credibility of outcomes, and publication bias was determined using Begg’s funnel plot and Egger’s test. Hazard ratio (HR) and 95% Confidence Intervals (CIs) were used to evaluate overall survival (OS) of HNSCC patients by univariate and multivariate analyses. Results: The dysregulated levels of 9 circRNAs (circPVT1, circCORO1C, circ_0000199, circCUX1, circPARD3, circMYC, circ_0102272, circ_0092125 and circ_00072387) were inversely related to OS of HNSCC patients [upregulated circRNA (univariate analysis: HR = 3.40, 95% CI: 2.66-4.36, p < 0.0001, I2 = 0%; multivariate analysis: HR = 3.33, 95% CI: 2.54-4.38, p < 0.0001, I2 = 0%), downregulated circRNA (univariate analysis: HR = 2.83, 95% CI: 1.73-4.65, p < 0.0001, I2 = 57.8%; multivariate analysis: HR = 2.35, 95% CI: 1.42-3.89, p = 0.0009, I2 = 0%)]. The individual HR for these 9 circRNAs indicated inverse relation to OS, validating the overall HR. The dyregulated levels of these circRNAs were also associated with poor clinicopathological outcomes such as primary tumor size, lymph node metastasis, distant metastasis and poor tumor (T), nodes (N), metastases (M); i.e TNM staging, and six of these circRNAs regulated diverse micro RNAs, revealing their role in tumorigenesis and cancer progression. Conclusion: Nine different circRNAs dysregulated in HNSCC tumors may serve as potential prognostic markers of HNSCC. These markers are associated with reduced OS and poor clinicopathological outcomes of HNSCC patients. They are also involved in the pathogenesis and progression of HNSCC through diverse mechanisms, and may serve as potential therapeutic targets.